Sudden death in the young adult: a Tunisian autopsy-based series - Saadi, Said (BMC Public Health, 2020)
BACKGROUND: We aim to study the profile, and pathological characteristics of sudden death in young in purpose of recommendations for prevention. METHODS: We performed a retrospective cohort study using autopsy data from the Department of Forensic Medicine of Monastir (Tunisia). A review of all autopsies performed for 28 years was done (August 1990 to December 2018). In each case, clinical information, and circumstances of death were obtained. A complete forensic autopsy and histological, and toxicological investigations were performed. We have included all sudden death in persons aged between 18 and 35 years. RESULTS: We collected 137 cases of sudden death during the studied period. The mean age of the studied population was 26.47 years. Almost 72% deaths were classified as cardiac death, and was due to ischemic heart disease in 32.32%. Sudden death was attributed to a pleuropulmonary cause in 7.4%, an abdominal cause in 6%, and from a neurological origin in 4.5%. The cause of sudden death in this group was not established by 9.5%. CONCLUSION: In this series, sudden death in young adults occurs mainly in a smoking male, aged between 18 and 24 years old, occurring at rest, in the morning, and early in the week. It is more common, especially in summer. Sudden death is most often the first manifestation of pathologies, especially unsuspected heart diseases. The predominance of cardiovascular causes is the common denominator of almost all studies reported in the literature. Our findings suggest that prevention of sudden death among young adults under the age of 35 years should also focus on evaluation for causes not associated with structural heart disease.